ASESMEN PERKEMBANGAN KOGNITIF DALAM PEMBELAJARAN ANAK USIA DINI - Masliani; Aslamiah; Darmiyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The golden age of early childhood is the period that underlies the next human life. In this period, children can hear, see, and imitate what they see, hear, and feel. Early childhood cognitive development is very important for child development, children need to be given cognitive stimulus to help other developmental stimuli. With cognitive stimulus, children can grow and develop well. By conducting an assessment of early childhood cognitive development, we can find out that each child has a different rate of cognitive development for each individual, what the child has not been able to achieve, find out what activity materials are considered inappropriate and materials so that teachers or parents can improve the methods and strategies that will be used. This assessment has a positive impact on the application of cognitive development, because it can improve the cognitive aspects of early childhood. Likewise with other aspects such as physical, social emotional, language, religious and moral values, and art. This paper aims to describe how cognitive development assessments in early childhood learning. This study uses a literature study method whose data sources are relevant and related to cognitive development assessments in early childhood learning. From the research results there are 4 stages of cognitive development including the sensory motor stage, pre-operational stage, concrete operational stage, and formal operational stage. There are several techniques and methods in assessing the education of children of this age, namely by observation, anecdotal notes, through conversation, through assignments, performance, work results, daily child development achievement scale (checklist), portfolio.